Comparative performance of the laboratory assays used by a Diagnostic Laboratory Hub for opportunistic infections in people living with HIV. (1st September 2020) - Medina, Narda; Alastruey-Izquierdo, Ana; Mercado, Danicela; Bonilla, Oscar; Pérez, Juan C.; Aguirre, Luis; Samayoa, Blanca; Arathoon, Eduardo; Denning, David W.; Rodriguez-Tudela, Juan Luis
Abstract : Objectives: We evaluated the comparative performance of different assays used in a Diagnostic Laboratory Hub that linked 13 HIV healthcare facilities for the diagnosis of tuberculosis (TB), histoplasmosis, and cryptococcosis, and describing its functions in Guatemala compared with other National Reference Laboratories. Methods: The following diagnostic techniques were analyzed in 24 months (2017–2018) in a cohort of patients with HIV: smear microscopy, mycobacterial and fungal cultures, isolator blood culture, PCR assays, and antigen detection tests. Results: A total of 4245 patients were included, 716 (16.2%) had an opportunistic infection: 249 (34.7%) TB, 40 (5.6%) nontuberculous mycobacteria, 227 (31.7%) histoplasmosis, 138 (19.3%) cryptococcosis, and 62 (8.6%) had multiple opportunistic infections. Two hundred sixty-three [92.6%; 95% confidence interval (CI), 89–95.1] of TB cases were diagnosed by PCR. Urine antigen assay detected 94% (95% CI, 89–96) of the disseminated histoplasmosis cases. A lateral flow assay to detect cryptococcal antigen diagnosed 97% (95% CI, 93.3–98.7%) of the cryptococcal cases. In 85 patients (51.5%) with a cerobrospinal fluid sample, cryptococcal meningitis was diagnosed in 55 (64.7%), of which 18 (32.7%) were only detected by cryptococcal antigen. Conclusion: Validated commercial antigen tests, as used in this program, should be the new gold standard for histoplasmosis and cryptococcosis diagnosis. In their absence, 35% of disseminated histoplasmosis and 32.7% of cryptococcal meningitis cases would have been missed. Patients with multiple opportunistic infections were frequently diagnosed and strategies should be designed to screen patients irrespective of their clinical presentation. In low resource settings, Diagnostic Laboratory Hubs can deliver quality diagnostics services in record time at affordable prices. Abstract : Supplemental Digital Content is available in the text